Modified TMV Particles as Beneficial Scaffolds to Present Sensor Enzymes - Koch, Claudia; Wabbel, Katrin; Eber, Fabian J.; Krolla-Sidenstein, Peter; Azucena, Carlos; Gliemann, Hartmut; Eiben, Sabine; Geiger, Fania; Wege, Christina (Frontiers in Plant Science, 2015)
Tobacco mosaic virus (TMV) is a robust nanotubular nucleoprotein scaffold increasingly employed for the high density presentation of functional molecules such as peptides, fluorescent dyes and antibodies. We report on its use as advantageous carrier for sensor enzymes. A TMV mutant with a cysteine residue exposed on every coat protein (CP) subunit (TMVCys) enabled the coupling of bifunctional maleimide-polyethylene glycol (PEG)-biotin linkers (TMVCys/Bio). Its surface was equipped with two streptavidin [SA]-conjugated enzymes: glucose oxidase ([SA]-GOx) and horseradish peroxidase ([SA]-HRP). At least 50 % of the CPs were decorated with a linker molecule, and all thereof with active enzymes. Upon use as adapter scaffolds in conventional 'high-binding' microtiter plates, TMV sticks allowed the immobilization of up to 45-fold higher catalytic activities than control samples with the same input of enzymes. Moreover, they increased storage stability and reusability in relation to enzymes applied directly to microtiter plate wells. The functionalized TMV adsorbed to solid supports showed a homogeneous distribution of the conjugated enzymes and structural integrity of the nanorods upon transmission electron and atomic force microscopy. The high surface-increase and steric accessibility of the viral scaffolds in combination with the biochemical environment provided by the plant viral coat may explain the beneficial effects. TMV can, thus, serve as a favorable multivalent nanoscale platform for the ordered presentation of bioactive proteins.